Specifics of supercritical parameters of a flow under non-uniform heating of the fuel assembly channel walls - Avramenko, A.A.; Kondratieva, E.A.; Kovetskaya М.М.; Tyrinov, A. I.; Vasilchenko, V.V. (Reports of the National Academy of Sciences of Ukraine, 2014)
Based on the RNG k-ε turbulence model, computer simulations are performed. Their results include distributions of the hydrodynamical and heat transfer parameters for a supercritical water flow in the seven-rod fuel assembly. The simulations were performed under steady state conditions at uniform and non-uniform heating of the channel walls, which enabled us to reveal effects of the heating on the distribution of the coolant properties. It is shown that the non-uniform heating an causes azimuthal non-uniformity of the heat transfer coefficient.